Development of Project-Based Learning Model Assisted by Mobility Orientation Technique Application (ATOM) for Students with Hearing Impairments - Dewi Ekasari Kusumastuti; Mirnawati Mirnawati; Eviani Damastuti; Dewi Juwita Susanti; Tenty Jahrina Ramli; Sulistyo Rini (STAI Hubbulwathan Duri, 2025)
Students with hearing impairments often face unique challenges in mobility orientation learning, particularly in mastering sighted guide techniques. This study aims to analyze their learning needs and develop a feasible, practical, and effective Project-Based Learning (PjBL) model supported by the Mobility Orientation Technique Application (ATOM). The research adopts the ADDIE development model, encompassing analysis, design, development, implementation, and evaluation stages. The study involved expert validations, product trials with students, and effectiveness testing through pre- and post-assessments. The analysis stage identified key learning needs among students with hearing impairments. The developed PjBL model, assisted by ATOM, was evaluated for feasibility through expert validation. Material experts rated it 4.34 and media experts 4.77 on a 5-point scale, indicating high feasibility. In product trials, the model received a practicality score of 3.11 from students, reflecting its ease of use and implementation. Effectiveness was demonstrated by a 21.7% increase in students' post-test scores, showing significant improvement in understanding sighted guide techniques. The results suggest that the integration of ATOM into a PjBL framework effectively addresses the learning needs of students with hearing impairments, offering a practical and impactful instructional approach in the mobility orientation course. The PjBL model assisted by ATOM is a feasible, practical, and effective learning solution for enhancing mobility orientation skills in students with hearing impairments, and holds promise for broader application in inclusive education settings.